Prevalence, spermatozoa, hormonal, and genetic evaluation of rare mosaic klinefelter syndrome patients in southern China - Li, Derong; Lai, Yuqing; Liao, Yujuan; Pan, Jinjie; Luo, Yudi; Liang, Yunning; Luo, Bowen; Zhu, Lingling; Deng, Guosheng; Li, Xiang; Feng, Keng; Lei, Feifei; et al. (Frontiers in Genetics, 2025)
BackgroundKlinefelter syndrome (KS) is the most common genetic cause of male infertility in humans. Mosaic KS is a subtype of KS. Due to its low prevalence, the lack of typical clinical signs, and the limited professional awareness of the syndrome, many cases of mosaic KS remain undiagnosed.ObjectiveTo investigate the prevalence of rare mosaic KS, karyotype characteristics, reproductive hormone levels, and sperm quality in southern China, and to enrich our knowledge of patients with mosaic KS.MethodsThe chromosome results of 8,110 cases of infertile male patients attending the Reproductive Center of Yulin Maternal and Child Health Hospital from January 2018 to July 2024 were retrospectively analyzed. Semen, sex hormone tests, and Y chromosome microdeletions were analyzed in fourteen selected patients with a diagnosis of mosaic KS.ResultsAmong the 8,110 male infertility patients, a total of 0.703% (57/8,110) were diagnosed with KS. Of these, 0.530% (43/8,110) had the typical non-mosaic chromosomal karyotype of 47, XXY, while 0.172% (14/8,110) demonstrated mosaicism. Non-mosaic KS accounted for 75.44% (43/57), whereas mosaic KS accounted for 24.56% (14/57). Among the fourteen patients diagnosed with mosaic KS, the predominant chromosomal karyotype was 47,XXY/46,XY, observed in eleven patients, accounting for 78.57% of the cases. Additionally, one patient exhibited a chromosomal karyotype of 47,XXY [29]/46,XX [78]. Another patient had 47,XXY [92]/48,XXXY [3]/46,XY [5], and a third patient presented with 47,XXY [87]/46,XX [3]/46,XY [2]. The semen analysis of individuals with mosaic KS revealed two cases of azoospermia, one case of cryptozoospermia, one case of severe oligospermia, one case of oligospermia, and ten cases of normal sperm. The results of the sex hormone analysis revealed abnormal increases in serum follicle-stimulating hormone (FSH) levels in four patients diagnosed with mosaic KS. Additionally, two patients with mosaic KS exhibited higher luteinizing hormone (LH) and testosterone (TT) levels compared to the normal range, while four patients had lower estradiol (E2) levels than the normal range. Among the fourteen patients with mosaic KS, four couples underwent assisted reproductive technology at our hospital for fertility assistance. Of these four couples, two successfully gave birth to a healthy child.ConclusionThe prevalence of mosaic KS among male infertility patients in southern China is 0.172% (14/8,110), with the predominant chromosomal karyotype being 47,XXY/46,XY, accounting for 78.57% (11/14) of the cases. Patients with mosaic KS may present with various sperm conditions, including azoospermia, cryptozoospermia, severe oligozoospermia, oligozoospermia, and normal sperm. There is a notable correlation between sperm count and the number of abnormal cell karyotypes in these patients; specifically, a higher number of abnormal chromosomal mosaic cells is associated with a lower sperm count. In comparison to non-mosaic KS patients, those with mosaic KS exhibit a lower rate of azoospermia. In summary, patients with rare mosaic KS in southern China demonstrate significant heterogeneity in sperm production, hormonal levels, and genetics. These patients can achieve biological fatherhood through assisted reproductive techniques, and mosaic KS does not appear to impact the success rate of these techniques. However, due to the low prevalence and limited sample size, more data is necessary to confirm these findings.